Intensive fodder production through legume intercropping in hybride napier - Jayakumar G (Department of Agronomy, College of Agriculture, 1997)
A field experiment was conducted at the instructional farm, Vellayani during 1995 – 1996 for studies on intensive fodder production through legume intercropping in hybrid napier. It was aimed to evaluate the performance of hybrid napier as influenced by planting geometrics, intercrops and nitrogen levels. The experiment was laid out in factorial Randomised Block Design. The abstract of the results is given below.